Increasing work-place healthiness with the probiotic Lactobacillus reuteri: A randomised, double-blind placebo-controlled study - Stan Vlaicu; Tubelius Py; Zachrisson Anders (BMC, 2005)
Abstract Background Short term illnesses, usually caused by respiratory or gastrointestinal diseases are disruptive to productivity and there is relatively little focus on preventative measures. This study examined the effect of the probiotic Lactobacillus reuteri protectis (ATCC55730) on its ability to improve work-place healthiness by reducing short term sick-leave caused by respiratory or gastrointestinal infections. Methods 262 employees at TetraPak in Sweden (day-workers and three-shift-workers) that were healthy at study start were randomised in a double-blind fashion to receive either a daily dose of 108 Colony Forming Units of L. reuteri or placebo for 80 days. The study products were administered with a drinking straw. 181 subjects complied with the study protocol, 94 were randomised to receive L. reuteri and 87 received placebo. Results In the placebo group 26.4% reported sick-leave for the defined causes during the study as compared with 10.6% in the L. reuteri group (p < 0.01). The frequency of sick-days was 0.9% in the placebo group and 0.4% in the L. reuteri group (p < 0.01). Among the 53 shift-workers, 33% in the placebo group reported sick during the study period as compared with none in the L. reuteri group(p < 0.005).